2020
DOI: 10.3390/ma13235536
|View full text |Cite
|
Sign up to set email alerts
|

Cold Expansion Process with Multiple Balls—Numerical Simulation and Comparison with Single Ball and Tapered Mandrels

Abstract: Cold expansion technology is an extended method used in aeronautics to increase fatigue life of holes and hence extending inspection intervals. During the cold expansion process, a mechanical mandrel is forced to pass along the hole generating compressive residual hoop stresses. The most widely accepted geometry for this mandrel is the tapered one and simpler options like balls have generally been rejected based on the non-conforming residual hoop stresses derived from their use. In this investigation a novelt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The authors of the work [9] applied finite element modeling and fatigue testing to compare residual hoop stresses induced by the cold expansion process using multiple balls with those arising from the cold expansion using a single ball and a tapered mandrel. The results showed that the use of three incremental balls significantly reduced the magnitude of non-conforming residual hoop stresses and the extension of this detrimental zone.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the work [9] applied finite element modeling and fatigue testing to compare residual hoop stresses induced by the cold expansion process using multiple balls with those arising from the cold expansion using a single ball and a tapered mandrel. The results showed that the use of three incremental balls significantly reduced the magnitude of non-conforming residual hoop stresses and the extension of this detrimental zone.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of split sleeves is generally considered a better method to protect the hole edge material from tearing and strong friction during mandrel and ball expansion [ 11 , 12 , 13 ]. Split sleeve cold expansion (SSCE) can not only avoid axial scratching of hole walls, but also has the advantages of good adaptability and high productivity, which lead to the wide application of SSCE in the aircraft assembly field [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the fatigue life of the hole structure, the cold expansion strengthening technology of compression bushings is widely used [7][8][9][10]. It can reduce the hole edge stress under external load and effectively inhibit the crack generation at the hole edge [11][12][13]. Compression bushings have been massively applied to the fatigue strengthening of the important joints of many aircraft models at home and abroad [14,15].…”
Section: Introductionmentioning
confidence: 99%